Enjeux des pratiques de littéracie numérique chez les étudiants de master FLE, futurs enseignants de langue : étude des représentations et des pratiques effectives - Élodie Lang; Sabrina Royer (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Research in digital sociocriticism highlights the importance of digital literacy beyond technical skills. This skill, which has become essential for teaching practice, raises considerations in language teaching. This research explores the links between action, representations, and engagement, highlighting the influence of social representations on action patterns. In this pre-study, our attention is focused on the involvement of future teachers in non-formalized technopedagogical practices. Based on observations of FFL master's students' reluctance to use digital technology, we seek to understand how to integrate digital literacy into training. The socio-cognitive analysis methodology will be based on the analysis of files submitted in different didactic courses and questionnaires to estimate the effectiveness of the digital practices of trainers. We examine the implicit model of technopedagogical practices, the preparation of students for the critical use of technopedagogies, and the way in which digital involvement leads to autonomy and the modification of representations.